EVALUASI KINERJA KEBIJAKAN RETRIBUSI PASAR REJOMULYO BERDASARKAN PERATURAN DAERAH NOMOR 2 TAHUN 2012 TENTANG RETRIBUSI JASA UMUM - Ardian Prasetyo; R. Slamet Santoso; Ari Subowo (Journal of Public Policy and Management Review, 2015)
Semarang city retribution that becomes an important component in the contribution of regional income is the retribution of Pasar Rejomulyo (Rejomulyo Market). In the implementation, the retribution tariff rule has not been relevant with the type of the group of places and the merchants based on the regional regulation. The purpose of the research was to evaluate the performance of retribution policy Pasar Rejomulyo based on the Regional Regulation Number 2 2012, from the consistency aspect of the setting and theoretic relevancy. The research used the descriptive qualitative type, with the informant from Market Office official and the merchants in Pasar Rejomulyo Semarang. The result of the research stated that Pasar Rejomulyo uses the mutual agreement to determine the retribution tariff. Besides, the retribution income cannot be proved, for there is no transparency of market retribution income. The conclusion is that Pasar Rejomlyo does not run the Regional Regulation Number 2 2012. The classification of the merchants based on their types; the enactment of retribution tariff and the provision of the basic area so that the Pasar Rejomulyo retribution can increase, needs to be done.